Evaluation of osteocalcin and pyridinium crosslinks of bone collagen as markers of bone turnover in gingival crevicular fluid during different stages of orthodontic treatment - Griffiths, G. S.; Moulson, A. M.; Petrie, A.; James, I. T. (Journal of clinical periodontology, 1998)
. Osteocalcin (Oc) and the collagen cross‐links pyridinoline (Pyr) and deoxypyridinoline (dPyr) arc used as markers of bone turnover in metabolic bone diseases. The aims of this study were: 1) to establish if Oc, Pyr and dPyr can be detected in GCF and 2) using the orthodontic tooth movement model of alveolar bone resorption to evaluate GCF levels of osteocalcin and these collagen cross‐links as markers of bone breakdown. Plaque, colour and bleeding indices, probing measurements and GCF samples were collected at two sites in each of 20 adolescents, during 4 stages of fixed appliance therapy: (1) prior to appliance lit. (2) post appliance fit, (3) during active retraction of the maxillary canines. (4) during retention. GCF was collected onto filter paper strips and the volume determined by weighing. An ELISA kit was used for the detection of osteocalcin, whereas Pyr and dPyr were assayed using high performance liquid chromotography (HPLC). Wilcoxon signed ranks test and Bonferroni correction revealed statistically significant increases in plaque (p= 0.012), GCF volume (p= 0.024) and osteocalcin concentration (p= 0.012). between stages 1 and 2. There were no statistically significant differences between the other variables at this stage or between any of the variables at stages 2 and 3, or between stages 3 and 4, All but 3 of the GCF samples yielded detectable osteocalcin, with large site and subject variation. The median values of osteocalcin and osteocalcin concentration of all the samples were 87.,5 pg and 66 pg/μl, with a range of 0–1,248 pg. 0–1,572 pg/μl. The detection of osteocalein in GCF during every stage, the wide variation between subjects, and the lack of a consistent pattern related to stages of orthodontic treatment, suggests that osteocalcin may merely be a constituent of GCF associated with the developing dentition, which would reduce its potential as a marker of bone turnover in this group. None of the 16 GCF samples analysed for Pyr and dPyr gave a positive result. This study confirms that fitting an orthodontic appliance results in plaque accumulation and increased gingival inflammation, and that GCF volume is the most sensitive indicator of that inflammation. Osteocalcin was detected in GCF collected from adolescents, whereas Pyr and dPyr could not be detected. Further work is required lo establish whether GCF osteocalcin levels can be used as a marker of bone turnover, and whether improvements in the sensitivity of detecting Pyr & dPyr make further study of these promising bone markers worthwhile.